The education of the future: the students' perspective. Validation of a scale - Sara Conde Vélez; Ángel Boza Carreño (Universidad de Guadalajara, 2019)
This article presents a study which aims to validate and optimize a scale of evaluation of the education of the future from the perspective of the students. To this end, we took a sample of 431 students on different degree courses at the University of Huelva (Spain). An ad hoc scale designated 'Future education' was drawn up for data collection, designed to assess the beliefs of students on the education of the future. Then the instrument was validated by Cronbach's alpha and the unidimensionality of the different subscales conducting a factorial analysis of principal components was assessed. The results corroborate that the proposed dimensions (context, teachers, methodology, students and competences) are unifactorial. The skills to be acquired in the future are strongly linked to life in virtual environments.